Sharing soil knowledge of the Congolese coastal plains within international research partnerships - Lydie-Stella Koutika (Soil Advances)
Soil knowledge is very limited in the Congolese coastal plains, while database from the colonial period is unavailable and scarce. These soils are commonly nutrient-poor, sandy, and regarded as unsuitable for agriculture. In recent decades, nature-based approaches such as afforestation have been implemented to sustain productivity, conserve natural forests, and improve soil fertility. Other goals of this approach are mitigating climate change and biodiversity loss and restoring degraded lands in contributing to the sustainable development goals (SDGs) of the United Nations Agenda 2030. This mini-review investigates forest and agroforestry systems, focusing on soil knowledge, especially regarding the introduction of nitrogen-fixing species (NFS). Increased carbon (C) and nitrogen (N) stocks, enhanced phosphorus (P) and sulphur (S) dynamics, and the structure and diversity of bacterial and fungal composition are reported. This highlights a strong network and collaboration in soil knowledge. However, the collaboration of stakeholders, NGOs, and policymakers remains weak. The future and strong interconnected soil, forest plantations and social-economic data sharing to tackle environmental challenges i.e., climate change, biodiversity loss, pollution, and soil and land degradation, is crucial and needed in the region.